Природно-заповідні території лісового фонду Волинської області - Павловська, Тетяна Сергіївна; Рудик, Олександр Володимирович; Ничипорук, Оксана Анатоліївна; Pavlovska, Tetiana S.; Rudyk, Oleksandr V.; Nychyporuk, Oksana A. (My University, 2017)
Представлено результати аналізу природно-заповідного фонду в межах лісів Волинського обласного управління лісового та мисливського господарства (ВОУЛМГ). З’ясовано структуру управління лісовим господарством. Охарактеризовано сучасну категоріальну структуру природно-заповідного фонду лісів ВОУЛМГ за кількістю та площею природно-заповідних територій. Проаналізовано динаміку розвитку природно-заповідного фонду на лісових землях упродовж останнього п’ятиріччя (2012−2016 рр.). Зроблено аналіз поширення природно-заповідних територій в розрізі держлісгоспів. Дослідження побудовано на матеріалах Волинського обласного управління лісового та мисливського господарства; основні результати проілюстровано діаграмами.

The results of the analysis of natural protected areas within the forests of Volyn Regional Office of a Forestry and Hunting (VROFH) are given. The structure of forest management is explained. The modern categorial structure of natural forest protected areas of VROFH is characterized according to the number and size of protected areas. The dynamics of natural reserve fund on forest land in the last five years (2012-2016) is analyzed. The analysis of arrangement of protected areas in the context of State Forestry are made. The study is based on materials of Volyn Regional Office of a Forestry and Hunting; the main results are illustrated with the diagrams.
Protected areas of forest fund of Volyn region
Keywords: коефіцієнт заповідності; ліс; лісове господарство; лісовий фонд; лісокористування; природно-заповідний фонд; природно-заповідні території; coefficient protected areas; forest; forestry; forest fund; forest management; natural reserved fund; natural protected areas